Acumulação de capacidades tecnológicas e mecanismos de aprendizagem: um estudo comparativo em duas subsidiárias de empresas multinacionais do setor de tecnologias da informação e comunicação no Brasil - Barros, Eliseu Alencar (2010)
This dissertation examines the relationship among the trajectory of accumulation of technological capabilities and its learning mechanism in subsidiaries of multinational companies in developing economies. This relationship is analyzed by a comparative case study of two Brazilian subsidiaries of the information technology and telecommunications sector, from different home country origins, for technologies associate to high speed internet access, from 2004 to 2009. Even though much has been written along the last years concerned about the accumulation of firm-level technological capabilities into the developing countries, describing many examples of this trajectories . Only a few studies has analyzed these aspects in subsidiaries of multinational companies, and fewer have analyzed the relationship of accumulation of technological capabilities and it’s learning mechanism in subsidiaries of multinational companies. Reaching out to contribute to the international literature, this dissertation search to enrich this debate, based on qualitative and quantitative evidences collected from primary and secondary sources to explore this relation and get the following results: 1. In both companies could be notice the accumulation of technological capabilities. But, this process was very distinct in both companies in tern of rate of the trajectory and the king of the technological capability. 2. Also, could be verified high usage of different levels of learning mechanisms, from different sources (intraorganizacionais from external sources and interorganizacionais from internal sources). But this characteristics also was very distinct in both companies, not only in intensity but also in diversity of learning mechanism. With that results this work points out, that the different mechanisms of technological learning used by the organizations in developing economies not only play a role of basic relevance for the nature of the accumulated technological capacities, but also for the accumulation intensity. And, that conclusion can be interpreted that the Brazilian subsidiary of Alcatel-Lucent, through its efforts of technological learning, is better prepared for a competitive context characterized by technological innovations then the subsidiary of ZTE Corporation. But this innovative competitive context, in many occasions in developing economies does not takes form, as the Brazilian case, due the low competition and the increase of the necessity of short term economic results, companies with the approach of costs (or low cost operation capacities) are more valued of what companies with the approach of development of innovative capacities capable to produce technologies. So, this conclusions suggest for the manages of those companies: (1) the necessity of a continuous enrollment in search of new sources of internal and external technological learning to its respective organizations, of form to support and to accumulate new operational and innovative technological capacities, (2) the importance of the quality and intensity of the different types of relations and interactions (internal and external) to intensify the learning relations in inexistent technologies in these organizations. And this conclusion also allow to point some suggestions to governmental politics. Due the 'National Plan of Broadband', in development for the Brazilian federal government should (1) partnerships and interactions between the diverse types of organizations as the subsidiary, operators and technological research centers and local universities, must be stimulated the reinforcement, to create mutual projects of R&D. And, as a consequence, these interaction will generate bigger technological development. (2) to target, thru regulation, that the companies must be persuaded to search new and better learning mechanisms for technological capabilities accumulation, foreseen the sector technological development.